A Study of Formulaic Language in Traditional Greek Tales and Its Cultural Implications in Language Teaching - Smaragda PAPADOPOULOU (Mehmet KURUDAYIOĞLU, 2016)
In our study we examine teaching mother tongue through faire and folk tales from the perspectives of recognizing clichés in fairy tales and myths, idiomatic phrases which work as morals, proverbs and very specific phrases of traditional tales'. We suggest that formulaic language can be involved in children's language games at school and become a methodological tool for innovative approaches in Language and Teaching especially at the primary education. We search the sources from Greek traditional tales that could serve as teaching material for this option of teaching formulaic language in mother tongue. Cultural and geographical implications of the examples applied are noted as a suggestion for further discussion.